THE IMPROVING STUDENTS’ INTEREST BY USING PUPPET MEDIA at SMALB-C TUTWURI HANDAYANI CIMAHI - Vina Ilmi Na'fiul Ardiah; Astry Andrianty (PROJECT (Professional Journal of English Education), 2018)
Education is the main thing for children to gain knowledge in school. In learning English, children with special needs has difficulty in learning. From this analysis, the writers do some research on children who have special needs to creasing their interest, enterprising and easy in learning English at SMALB-C Tutuwuri Handayani Cimahi. Researcher hope, in this research is able to remind people’s awarness and the government to children with special needs in providing education. Because, they have the same rights in education. The reseacher was conducted entitle “The Improving Students’ Interest by Using Puppet Media”. This research, the use puppet media as one of the tools teaching to increase students’ interest and improve their vocabulary in learning English. The use of puppet as media with technique matching the puppet with the word.  The reseacher took in class X and XI, in class X there are 2 students and class XI there are 3 students, so we combine there are 5 students. This study used an oral test, obervation checklist and interview for collecting data. Researcher have found the results of the research and observations of the students. The result of the students 75% improve their interst, improved their writing 65 %, improved their speaking 60%, improve their vocabulary and speech 65%, recognize matching puppet process 70%, participate in class 35%. From the observation above, the researcher is conviced that the use of puppet as one of media can increase the students’ interest and vocabulary in learning English.